Climate and topographic controls on simulated pasture production in a semiarid Mediterranean watershed with scattered tree cover - Lozano-Parra, J; Maneta, M P; Schnabel, S (HYDROLOGY AND EARTH SYSTEM SCIENCES, 2014)
Natural grasses in semiarid rangelands constitute an effective protection against soil erosion and degradation, are a source of natural food for livestock and play a critical role in the hydrologic cycle by contributing to the uptake and transpiration of water. However, natural pastures are threatened by land abandonment and the consequent encroachment of shrubs and trees as well as by changing climatic conditions. In spite of their ecological and economic importance, the spatiotemporal variations of pasture production at the decadal-century scales over whole watersheds are poorly known. We used a physically based, spatially distributed ecohydrologic model applied to a 99.5 ha semiarid watershed in western Spain to investigate the sensitivity of pasture production to climate variability. The ecohydrologic model was run using a 300-year-long synthetic daily climate data set generated using a stochastic weather generator. The data set reproduced the range of climatic variations observed under the current climate. Results indicated that variation of pasture production largely depended on factors that also determined the availability of soil moisture such as the temporal distribution of precipitation, topography, and tree canopy cover. The latter is negatively related with production, reflecting the importance of rainfall and light interception, as well as water consumption by trees. Valley bottoms and flat areas in the lower parts of the catchment are characterized by higher pasture production but more interannual variability. A quantitative assessment of the quality of the simulations showed that ecohydrologic models are a valuable tool to investigate long-term (century scale) water and energy fluxes, as well as vegetation dynamics, in semiarid rangelands.
APS
Keywords: degradation; ecohydrology; Grasslands; pasture production; semiarid rangelands; soil erosion